De la temporalité aux relations logiques : l’évolution de quelques locutions conjonctives en français - Bernard Combettes (Studii de Lingvistica, 2023)
This study focuses on the semantic evolution of certain conjunctive phrases that lose their temporal value and take on logical values of causality and opposition. We examine the locutions that express simultaneity (tandis que, alors que, pendant que) and that evolve towards opposition, then those that express posteriority (puisque, dès que) and that evolve towards causality. The case of expressions formed on nouns (à l’instant que) is treated separately. We will try to observe differences in the speed of change depending on whether the expressions are of earlier or later formation, and to establish a chronology of this evolution by showing the particular importance of the pre-classical French period.